Comparison and Optimization of Parameters of Axialflow Blowers - Datta, A C; Das, Samir Kumar; Pandya, A C (Journal of Agricultural Engineering, 2002)
Air-carrier sprayers provide functional, operational and economic advantages over the use of sell-propelled and tractor mounted hydraulic sprayers for the control of diseases and pests in plantation crops. This paper describes the performance characteristics of output air-jet from two axial-flow blowers of different designs - domestic blower A (operated using 8, 10, 12 and 14 blades at 2030, 2200, 2350, 2550 and 2730 rpm) and blower B (operated using 10 blades at 2130,2232,2332,2445,2535 and 2658 rpm., and at 0.714, 0.743 and 0.767 stagger angle ratio). Air-jet characteristics of both the blowers were evaluated and established the effects of operating speed, number of blades and stagger angle ratio. Each of these parameters was optimized statistically and using the technique of dimensional analysis. The blower A was then modified using these optimum parameters and blade type similar to that in blower B to obtain a new blower C. This blower provided better efficiency and higher air parameters for operation with a 26.25 kW tractor at 2380 rpm.